Context‐induced relapse to cocaine seeking after punishment‐imposed abstinence is associated with activation of cortical and subcortical brain regions. (29th June 2017) - Pelloux, Yann; Hoots, Jennifer K.; Cifani, Carlo; Adhikary, Sweta; Martin, Jennifer; Minier‐Toribio, Angelica; Bossert, Jennifer M.; Shaham, Yavin
Abstract: We recently developed a rat model of context‐induced relapse to alcohol seeking after punishment‐imposed abstinence to mimic relapse after self‐imposed abstinence due to adverse consequences of drug use. Here, we determined the model's generality to cocaine and have begun to explore brain mechanisms of context‐induced relapse to cocaine seeking after punishment‐imposed abstinence, using the activity marker Fos. In exp. 1, we trained rats to self‐administer cocaine (0.75 mg/kg/infusion, 6 hours/day, 12 days) in context A. Next, we transferred them to context B where for the paired group, but not unpaired group, 50 percent of cocaine‐reinforced lever presses caused aversive footshock. We then tested the rats for cocaine seeking under extinction conditions in contexts A and B. We also retested them for relapse after retraining in context A and repunishment in context B. In exp. 2, we used Fos immunoreactivity to determine relapse‐associated neuronal activation in brain regions of rats exposed to context A, context B or neither context. Results showed the selective shock‐induced suppression of cocaine self‐administration and context‐induced relapse after punishment‐imposed abstinence in rats exposed to paired, but not unpaired, footshock. Additionally, context‐induced relapse was associated with selective activation of dorsal and ventral medial prefrontal cortex, anterior insula, dorsal striatum, basolateral amygdala, paraventricular nucleus of the thalamus, lateral habenula, substantia nigra, ventral subiculum, and dorsal raphe, but not nucleus accumbens, central amygdala, lateral hypothalamus, ventral tegmental area and other brain regions. Together, context‐induced relapse after punishment‐imposed abstinence generalizes to rats with a history of cocaine self‐administration and is associated with selective activation of cortical and subcortical regions. Abstract : We recently developed a rat model of context‐induced relapse to alcohol seeking after punishment‐imposed abstinence to mimic relapse after self‐imposed abstinence due to adverse consequences of drug use. Here, we determined the model's generality to cocaine and have begun to explore brain mechanisms of context‐induced relapse to cocaine seeking after punishment‐imposed abstinence, using the activity marker Fos. We showed the context‐induced relapse after punishment‐imposed abstinence generalizes to rats with a history of cocaine self‐administration and is associated with selective activation of cortical and subcortical regions.